Comparative Advantage in Interntional Trade: A Study Based on Leading Exports in Sri Lanka - KMV Sachithra; GAC Sajeevi; MPK Withanawasm; WMSA Jayathilake (Kelaniya Journal of Management, 2014)
The export and import economic policy has both advantages and disadvantages. In Sri Lanka, however, export and import economy led to unsymmetrical export portfolio, which has continuously outcome for deficit trade balances. The main objective of this study is to identify international competiveness of Sri Lankan exports. Revealed Symmetric Comparative Advantage (RSCA) indices use to identify the trade pattern, the sectors in which an economy has a comparative advantage, by comparing the country of interests’ trade profile with the world average. Trade Balance Index (TBI) is employed to analyze whether a country has specialization in export (as net-exporter) or in import (as net-importer) for a specific group of products. This paper concludes that even though, Sri Lanka has comparative advantage for leading exports, it does not provide significant contribution to overcome negative impact of comparative disadvantage and net import products. DOI: http://dx.doi.org/10.4038/kjm.v1i2.6453 Kelaniya Journal of Management Vol.1(2) 2012:51-85